FREE VIBRATION ANALYSIS OF ISOTROPIC AND ORTHOTROPIC CLAMPED PLATES USING ENERGY APPROACH (Sciences & Technologie. B, Sciences de l'ingénieur, 2004)
The free vibration of isotropic, orthotropic clamped rectangular plates using the Rayleigh-Ritz energy approach has been studied. The solution of the eigenvalue problem is obtained by assuming a deflected shape in the form of series functions that satisfy the edge boundary conditions of the plate. Simplified analytical expressions for frequencies are obtained that describe the vibrational characteristics of the plate. To demonstrate the accuracy of the present approach the same plate is discritisated  and  analyzed using the finite element method and the corresponding frequencies are obtained. The frequencies obtained with energy approach agree closely with those of the conventional finite element method.